A clinical validation study for the feasibility and reliability of three-dimensional ultrasound-ultrasound automatic image registration. (17th November 2015) - Su, Zhongzhen; Li, Kai; Xu, Erjiao; Wu, Lili; Wang, Xiaoli; Li, Liujun; Wang, Jue; Lin, Peijie; Chen, Yinan; Zhang, Yuan; Li, Junbo; Dufour, Cecile; et al.
Abstract: Purpose : The purpose of our study was to assess the feasibility and reliability of 3D ultrasound-ultrasound (US-US) automatic registration-based analysis of the hepatic vessel tree (VT) (3D VT-based automatic registration) in clinical applications. Materials and methods : A total of 70 pairs of 3D ultrasound data were acquired from the livers of 10 healthy volunteers enrolled in the study. An automatic registration method was applied to the acquired volumetric data pairs, and anatomic landmarks were picked by an experienced sonographer as 'ground truth'. The influences of respiration phase, subject posture, and liver lobe on data acquisition and scan volumetric angle on the registration accuracy and robustness were investigated. The registration time, success rate, median registration error distance, and sonographer's subjective feedback were assessed. Results : The time required for the 3D VT-based automatic registration was approximately 15∼20 s. Overall, the success rate for the hepatic vessel-based registration was 71% (50/70), and the median registration error distance was 1.72 mm (0.57∼4.71 mm). When the influential factors were well controlled, the optimal registration accuracy (median registration error distance = 1.22 mm) could be obtained with an excellent success rate of 100% (10/10). According to the subjective assessment of the sonographer, over 90% (45/50) of the automatic registration results were not inferior to the ground truth. Among them, 42% (21/50) were superior to the fusion results from the ground truth. Conclusions : The results suggest that the 3D VT-based automatic registration is feasible and reliable and has potential for guidance and evaluation of intraoperative ablation of hepatocellular carcinoma.